Level of anxiety and internal tryout evaluation of the national objective structured clinical examinations (OSCE) results for pharmacy students - Astuti, Engrid Juni; Hidayati, Ika Ratna (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2022)
OSCE (Objective Structured Clinical Examination) for pharmacist profession students is currently one of the measuring tools for success in competency exams to test victory in learning the Pharmacist Profession, in addition to the MCQ (Cognitive Based Test) method which is carried out in the form of CBT (Computer Based-Test). The Pharmacist Profession Study Program at the University of Muhammadiyah Malang (UMM) currently has professional pharmacist students and conducted a national tryout test for batch 2 students. In contrast, these students have never received training for the OSCE exam before. This study was conducted to evaluate the internal tryout on the results of the national OSCE score for Pharmacist students at the University of Muhammadiyah Malang” in batch 3 compared to batch 2, which had not done an internal tryout. In addition, an anxiety test was conducted on students taking the OSCE exam to get the degree of anxiety students taking the exam. From the study results, the anxiety level of the 2nd and 3rd batch students when facing the national OSCE exam was moderately anxious. Implementing the internal tryout had significant effects on the passing rate of the 3rd batch of students in the national OSCE exam.